Zakres odpowiedzialności pracodawców wobec rodzin pracowników w Drugiej Rzeczypospolitej - Grata, Paweł (Annales. Etyka w Życiu Gospodarczym, 2016)
The aim of this article is the presentation of the range of responsibility of employers towards workers’ families in Poland in the interwar period. The article also shows how these duties were realised. This problem appeared in Europe with the development of a social insurance programme and labour law. The Second Republic of Poland built its own law system for employees’ families. It included health insurance and benefits, families’ pensions and funeral allowances. Certain obligations were also imposed on employers in the context of labour law. The most important was the obligation to open nursery schools for children of women who worked in factories.